Perlindungan Satwa Langka Berdasarkan Asean Aggrement On The Conservation of Nature and Nature Resources 1985 - Kainama, Clif; Hanafi, Irma Halima; Daties, Dyah Ridhul Airin (PATTIMURA Law Study Review, 2025)
The 1985 ASEAN Agreement on the Conservation of Nature and Nature Resources states that ASEAN member states have responsibilities for wildlife in terms of protecting endangered species, conserving endemic species and implementing policies under their authority to prevent the extinction of species and subspecies. Article 5 of the agreement regulates endangered and endemic species, which states must register endangered species and take special measures. In relation to endangered wildlife, member states are responsible for prohibiting the hunting of such species; regulating the trade and possession and products of such species; protecting the habitats of such species; taking necessary policies to improve their conservation status and restore their populations to the highest level. This type of research is normative juridical where the research is carried out by collecting primary, secondary and tertiary data obtained using literature studies. The data that has been collected is analyzed qualitatively in which the description is arranged systematically based on legal disciplines to achieve clarity of the problems to be discussed. The results of this study show that animal protection is regulated in Article 3 of the ASEAN Agreement on the Conservation of Nature and Natural Resources: “The Contracting Parties shall, wherever possible, maintain maximum genetic diversity by taking action aimed at ensuring the survival and promoting the conservation of all species under their jurisdiction and control”.